(untitled) (Research, Society and Development, 2025)
Chronic neuropathic pain is a complex and debilitating condition that significantly compromises patients’ quality of life and shows limited response to conventional analgesics. In this context, antidepressants emerge as a relevant pharmacological alternative, as they act on the modulation of monoaminergic pain pathways and exhibit analgesic effects independent of their antidepressant action. The objective was to analyze the efficacy and safety of antidepressants in the management of chronic neuropathic pain. To this end, an integrative review of clinical studies, systematic reviews, and meta-analyses indexed between January 1, 2020, and October 10, 2025, was conducted, using the descriptors “antidepressants,” “neuropathic pain,” and “pharmacological treatment” in the Google Scholar, PubMed, and SciELO databases. Studies indicate that tricyclic antidepressants, such as amitriptyline, and serotoninnorepinephrine reuptake inhibitors (SNRIs), such as duloxetine and venlafaxine, demonstrate consistent efficacy in relieving neuropathic pain, especially in cases of diabetic neuropathy and pos-therpetic neuralgia. In addition to pain reduction, improvements in mood and patient functionality have been observed. The main reported adverse effects include nausea, drowsiness, and dizziness, generally of mild to moderate intensity. It is concluded that between 2020 and 2025, evidence reinforces that antidepressants, particularly TCAs and SNRIs, are effective and safe therapeutic options in the management of chronic neuropathic pain and should be used in an individualized manner according to the patient’s clinical profile.